MEASURING STUDENTS’ SATISFACTION TOWARDS STATE POLYTECHNIC OF CILACAP SERVICE QUALITY (SERVQUAL) WITH IMPORTANCE PERFORMANCE ANALYSIS METHOD - Ganjar Ndaru Ikhtiagung (Pro Bisnis, 2017)
This research is a research to measure the service quality (SERVQUAL) at State Polytechnic of Cilacap towards students’ satisfaction. The result of this research aims to give evaluation about service quality aspect at State Polytechnic of Cilacap (PNC) as stated in the National Regulation No. 25/2009 about Public Service. Method used in this research is by using Importance Performance Analysis. This technique used analysis in Frequency & Descriptive to describe the gap between the importance/expectation/priority and customers’ satisfaction/performance towards PNC’s service satisfaction. The total subjects in this research are 98 Electrical Engineering students, 138 Mechanical Engineering students, and 114 Informatics Engineering students. The effect of this research was shown in Cartesian coordinate system and Customer Satisfaction Index (CSI) analysis. From the result of them, it can be concluded that PNC needed to improve its service quality (ServQual). The attributes that work as the main priority of this case is the attribute in A quadrant, i.e. the cleanliness and tidiness of classrooms and the facilities in the laboratories. The second priority needed to improve is the attribute in C quadrant, i.e. 1) administration policy, 2) cleanliness of the bathroom, 3) administration handling, 4) campus atmosphere, 5) facilities in the classroom, 6) service procedure, 7) lecturers ability to understand students, 8) responsiveness of the employees, 9) internet access, 10) lecturers control on the students’ study, and 11) parking area. The most important and the ideal attribute to develop is the attribute in B quadrant. The excessive attribute is the attribute in D quadrant. CSI calculation is needed to calculate the students’ satisfaction. The result of this calculation showed that 62,61% of the students showed “Somewhat Satisfied” in the students’ satisfaction option.